2005
DOI: 10.1128/jcm.43.9.4654-4658.2005
|View full text |Cite
|
Sign up to set email alerts
|

Search for Localized Dysbiosis in Crohn's Disease Ulcerations by Temporal Temperature Gradient Gel Electrophoresis of 16S rRNA

Abstract: The mucosa-associated microbiota lining the gut epithelium might play a central role in the activation and/or perpetuation of mucosal inflammation in Crohn's disease (CD). We sought for localized dysbiosis by comparing the biodiversity and composition of the microbiotas in ulcerated and nonulcerated mucosal samples from patients with CD. Biopsy samples (n ‫؍‬ 75) of ulcerated and adjacent nonulcerated mucosa were collected during colonoscopy from 15 patients, from the ileum, right colon, left colon, and rectum… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
44
1

Year Published

2005
2005
2014
2014

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 74 publications
(50 citation statements)
references
References 32 publications
5
44
1
Order By: Relevance
“…This is in agreement with the recent findings of Eckburg and colleagues (3) but is somewhat surprising since several of our analyses compared inflamed and healthy tissues. A previous study of CD patients by use of temporal temperature gradient gel electrophoresis has also shown that ulcerated and nonulcerated tissues are similar in dominant-species composition (20). These findings suggest that it is unlikely that inflammation is directly caused by a mucosa-associated pathogen, a conclusion also reached by another group using a different methodology (22).…”
Section: Resultssupporting
confidence: 69%
“…This is in agreement with the recent findings of Eckburg and colleagues (3) but is somewhat surprising since several of our analyses compared inflamed and healthy tissues. A previous study of CD patients by use of temporal temperature gradient gel electrophoresis has also shown that ulcerated and nonulcerated tissues are similar in dominant-species composition (20). These findings suggest that it is unlikely that inflammation is directly caused by a mucosa-associated pathogen, a conclusion also reached by another group using a different methodology (22).…”
Section: Resultssupporting
confidence: 69%
“…Some authors reported increased numbers of aerobic Gram-negative rods (E. coli), while others found increased numbers of non-spore forming anaerobes (Proteobacteria and Bacteroides) and decreased numbers of spore-forming anaerobes like Clostridium [20][21][22][23][24] . There are also papers in which the authors found no differences between the bacterial flora in inflamed and non-inflamed tissue in the same patient [25,26] . On the contrary, Sepehri et al [27] using a PCR method showed significant differences in bacterial flora between the inflamed and non-inflamed mucosa, and an increase in microbial diversity in controls and the non-inflamed tissue from adult IBD patients.…”
Section: Discussionmentioning
confidence: 99%
“…TTGE is a culture-independent molecular method that has proven most appropriate in dynamic studies of dominant species diversity within complex ecosystems like the colon (8). The repeatability of amplifications with the universal primers used, and TTGE runs using the same starting sample, has already been shown (16,19). Furthermore, in all cases, a clear limit of detection was observed when the minority species accounted for 1:100 or less of the total DNA concentration (15,17).…”
Section: Discussionmentioning
confidence: 99%